Happy like this - Wurzbacher, Ashley, 1985- (John Simmons short fiction award., 2019)
"Spanning a wide range of distinct perspectives, voices, styles, and settings, the ten shimmering stories in Happy Like This offer lyrical, deeply felt, often humorous meditations on the complexity of choice and the ambiguity of happiness. Two identical twins watch their bodies and lives diverge as one of them takes up competitive bodybuilding. A part-time mermaid struggles with her fluid sexuality and turbulent romantic past when she finds herself working at her ex-girlfriend's child's birthday party. An up-and-coming sociologist studies factitious disorders in a group of young women, observing their daily lives and attempting to understand their experiences of self-harm. A ballerina must choose between motherhood and her art. The characters in Happy Like This are smart girls and professional women--social scientists, linguists, speech therapists, plant physiologists, dancers--who search for happiness in roles and relationships that are often unscripted or unconventional. In the midst of their ambivalence about marriage, monogamy, and motherhood and their struggles to accept and love their bodies, they look to other women for solidarity, stability, and validation. Sometimes they find it; sometimes they don't. Plucky yet vulnerable, knowledgeable yet needy, Ashley Wurzbacher's vividly-imagined characters invite us to ask: What does it mean to be happy? When every choice entails a loss, how can we feel like we're doing the right thing?"--